Virtual summer schools: experiences from Finland and Germany - Maximilian Köster; Sushant Raj Passi; Felix Bitterer; Ulla Vuorinen; Nermin Karaoglu (University of Groningen Press, 2022)
Summer schools are an important element of universities' international strategies. During the COVID-19 pandemic, however, they often had to be canceled due to health-related concerns and political guidelines. The partner universities A (Finland) and B (Germany) decided to offer their summer schools in a virtual format in 2021 to allow students to gain international experience from their home country and to maintain international relations during the pandemic. By evaluating the success of their summer schools and sharing their experiences, they found that virtual summer schools have great potential. For certain students (with jobs, limited financial resources, mobility impairments, families to care for, etc.), virtual summer schools are particularly suitable and might even represent the only possibility to gain international experience. For virtual summer schools to be successful, however, universities have to consider organizational and pedagogical questions. In this article, organizers from A and B share their lessons learned as an inspiration for other institutions planning virtual summer schools that are immersive and engaging.